Modeling phosphate adsorption of semi-intensive shrimp pond sediment - Nguyen, Van Huy (ĐHQGHN, 2017)
Models to simulate phosphate adsorption could be useful for predicting water quality and for controlling eutrophication of ponds and lagoons. The different models of phosphate dsorption of aquaculture pond sediment were investigated, including kinetic adsorption models and adsorption isotherm models. Five sediment samples were collected from 5 different semi- intensive shrimp ponds and analyzed physical and chemical properties. We m easured the p adsorption under different conditions o f pH and PO 4 -P concentration (pH 5, 7, and 8.5; 0 .5 -5 mg L ') in batch tests at a sediment-to-solution ratio o f 1:10 and then the experimental data was simulated by using several adsorption models . Results showed that p adsorption was not greatly affected by pH (p>0.05). This is probably attributed to the high proportion o f sand in sediment (>60%) which would have a low specific surface area and less reactive adsorption sites. The adsorption o f p with initial concentrations o f 0.5 and 5 mg L ' increased within the first 10 and 30 minutes o f incubation, respectively. The Langmuir model satisfactorily described the properties of padsorption isotherms of aquaculture pond sediment. According to the Langmuirmodel the maximum adsorption capacity was 0.275 ± 0.011mg g'